2008
DOI: 10.1152/advan.00101.2007
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative group testing benefits high- and low-performing students

Abstract: We used collaborative group testing in a veterinary physiology course (65 students) to test the hypothesis that all students (e.g., high-performing and low-performing students of each group) benefit from collaborative group testing. In this format, students answered questions in the traditional format as individuals. Immediately after completing the exam as individuals, students answered the same questions in groups of two, and, finally, the same questions were discussed by the instructor and students. We meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
81
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(108 citation statements)
references
References 22 publications
19
81
2
Order By: Relevance
“…17,56 Interestingly, this arrangement is not thought to be detrimental to high-achieving students, because they will nonetheless benefit from the discussion and group feedback. 17,21,27,54 The issue of "freeloading" is thought not to be problematic in smaller-sized groups (three to four persons) as in the present study. 55 While students in the collaborative groups may become dependent on others' preparation for the assessment (ie, "freeload"), most comments from the experimental group state a level of peer pressure that promoted studying and participation.…”
Section: Student Satisfactionmentioning
confidence: 59%
See 3 more Smart Citations
“…17,56 Interestingly, this arrangement is not thought to be detrimental to high-achieving students, because they will nonetheless benefit from the discussion and group feedback. 17,21,27,54 The issue of "freeloading" is thought not to be problematic in smaller-sized groups (three to four persons) as in the present study. 55 While students in the collaborative groups may become dependent on others' preparation for the assessment (ie, "freeload"), most comments from the experimental group state a level of peer pressure that promoted studying and participation.…”
Section: Student Satisfactionmentioning
confidence: 59%
“…18 Results from student attitude surveys confirm that collaborative testers have more positive attitudes toward the testing process in general compared to students who take assessments individually. 11,[19][20][21] It should be noted, however, that when students are exposed to traditional teaching methods but tested in a collaborative manner, they may not perform as well on higher-level theory questions even if performance on lower-level concept questions is improved. 11,19 While researching the effects of collaborative testing on test performance without prior collaborative learning, Breedlove and colleagues reported that the effects of collaborative testing were directly related to the level of cognitive processing required by the test question.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Encouraging group work and peer discussions, along with other cooperative strategies, may lead to better student learning outcomes. Experts thus suggest that these approaches should be used in conjunction with, or even instead of, lectures [7][8][9][10][11][12] . Such teaching strategies are consistent with the Vygotskian perspective that learning is built socially through participants' interaction with each other throughout the process of assimilating new knowledge 13 .…”
Section: Introductionmentioning
confidence: 99%